Gentiopicroside improves non-alcoholic steatohepatitis by activating PPARα and suppressing HIF1 - Huang, Chaoyuan; Yong, Qiuhong; Lu, Yihui; Wang, Lu; Zheng, Yiyuan; Zhao, Lina; Li, Peiwu; Peng, Chong; Jia, Wei; Liu, Fengbin (Frontiers in Pharmacology, 2024)
Gentiopicroside (GPS) is a highly water-soluble small-molecule drug and the main bioactive secoiridoid glycoside of Gentiana scabra that has been shown to have hepatoprotective effects against non-alcoholic steatohepatitis (NASH), a form of non-alcoholic fatty liver disease (NAFLD) that can progress to cirrhosis and hepatocellular carcinoma. However, the effects of GPS on NASH and the underlying mechanisms remain obscure. Firstly, a high-fat, high-cholesterol (HFHC) diet and a highsugar solution containing d-fructose and d-glucose were used to establish a nonalcoholic steatohepatitis (NASH) mice model. Secondly, we confirmed GPS supplementation improved metabolic abnormalities reduced inflammation, and ameliorated pathological damage in mice induced by highfat, high-cholesterol diet. Then we used metabolomics to investigate the mechanisms by which GPS treats NASH in mice. Metabolomics analysis showed GPS may work through the Peroxisome Proliferator-Activated Receptor (PPAR) signaling pathway and glycine, serine, and threonine metabolism. Functional metabolites restored by GPS included serine, glycine, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA). Western blot and qRT-PCR analysis confirmed GPS improved NASH by regulating PPARα and Hypoxia-Inducible Factor-1α (HIF-1α) signaling pathways. In vitro, studies further demonstrated EPA and DHA enhanced fatty acid oxidation through the PPARα pathway, while serine and glycine inhibited oxidative stress through the HIF-1α pathway in palmitic acid-stimulated HepG2 cells. Our results suggest GPS's anti-inflammatory and anti-steatosis effects in NASH progression are related to the suppression of HIF-1α through the restoration of L-serine and glycine and the activation of PPARα through increased EPA and DHA.